Characterization and antioxidant activity of semi-purified extracts and pure delphinidin-glycosides from eggplant peel (Solanum melongena L.). (January 2016) - Braga, Pier Carlo; Lo Scalzo, Roberto; Dal Sasso, Monica; Lattuada, Norma; Greco, Valentina; Fibiani, Marta
Highlights: Nasunin (NAS) and delphinidin-3-rutinoside (D3R) are the main eggplant anthocyanins. Pure and semi-purified NAS and D3R were compared with different antioxidant assays. Other antioxidants than anthocyanins are present in semi-purified extracts. Semi-purified extracts have higher antioxidant capacity than pure anthocyanins. NAS generally showed higher activity than D3R at the same molar concentration. Abstract: Eggplant peels containing delphinidin-3-rutinoside or delphinidin-3-( p -coumaroylrutinoside)-5-glucoside (nasunin) were compared and characterized for antioxidant properties, using three cell-free assays with electron paramagnetic resonance (EPR) and two biological assays on human neutrophils with luminol amplified chemiluminescence (LACL). Antioxidant solutions were made with semi-purified extracts depleted in chlorogenic acid or with purified anthocyanin crystals. The semi-purified nasunin extract was higher in scavenging capacity than delphinidin-3-rutinoside in four assays (superoxide anion, hydroxyl radical, LACL, and Fremy's salt). Nasunin crystals showed higher antioxidant indices in Fremy's salt and LACL assays, with no detectable activity against the hydroxyl radical. The EC50 against free radicals was 0.4–20.6 nmol/mL in semi-purified extracts, and 1.7–73.6 nmol/mL for anthocyanin crystals. The higher activity of semi-purified extracts than crystals was attributed to other antioxidants, such as ascorbic acid, glutathione and biogenic amines, thus representing a percentage close to 30% of the total antioxidant content of eggplant peels.